From archaeological artefact to unlimited heritage concept; Redefining museum collection in the disruption era - Akbar, Ali (Wacana, Journal of the Humanities of Indonesia, 2019)
The last two decades show how artefacts and heritage that have become museum collections have experienced the development of meaning. Along with that, disruption era, a period filled with changes caused by new innovations, which results in instability, during the last decade has affected various lines of life including museums. Meanwhile, the study on disruptive impacts on museums is considered rare, and specific studies in Indonesia, mainly in Jakarta, have not been found. This paper discusses the change of visitors’ point of view on collection and the strategy to invite the public so that they are willing to visit museums during this time. The methods used in this research are literature studies, observation, and predictive analysis by applying the theory of disruptive innovation (King and Baatartogtokh 2015). It is concluded that museums should display real collection as well as intangible culture, try to present real natural environment, increase community members’ participation, and keep themselves up-to-date with socio-cultural changes in the society.